Determination of the General Circulation of the Ocean and the Marine Geoid Using Satellite Altimetry. - Wunsch,Carl (1980)
This contract was the continuation of a previous one for the general purpose of understanding the use of satellite altimetry in physical oceanography. There have been several activities, some of which are continuing. We have published a paper demonstrating a general formalism for using altimetry for the joint purpose of determining the general circulation of the oceans and improving the geoid. Using conventional hydrography in the North Atlantic Ocean, a sea surface relative to the geoid has been constructed and will soon be published. The general problem of constructing marine geoids independent of altimetric measurements has been solved in the context of inverse theory. Such geoids are required for subtraction from an altimetric surface to find the ocean current signal. Finally, the principal investigator has been involved in the active planning for a proposed new altimetric mission called TOPEX. (Author)